First two fungemia cases caused by Candida haemulonii var. vulnera in China with emerged antifungal resistance - Chen, Xin-Fei; Hou, Xin; Zhang, Han; Jia, Xin-Miao; Ning, Li-Ping; Cao, Wei; Fan, Xin; Huang, Jing-Jing; Yang, Wen-Hang; Zhang, Ge; Zhang, Jing-Jia; Kang, Wei; et al. (Frontiers in Microbiology, 2022)
Candida haemulonii var. vulnera is a rare variant of C. haemulonii, which has been previously reported to cause human infections. Owing to the close kinship between C. haemulonii sensu stricto and C. haemulonii var. vulnera, accurate identification of C. haemulonii var. vulnera relied on DNA sequencing assay targeting, for example, rDNA internal transcribed spacer (ITS) region. In this work, two strains of C. haemulonii var. vulnera were collected from the China Hospital Invasive Fungal Surveillance Net (CHIF-NET). The identification capacity of three matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and VITEK 2 YST ID biochemical methods were evaluated against ITS sequencing. In addition, antifungal susceptibility testing was performed using Sensititre YeastOne. Moreover, we comprehensively screened drug-resistant related genes by whole-genome sequencing. The two strains were not correctly identified to species variant level using MALDI-TOF MS and YST ID cards. Both strains were resistant to amphotericin B (minimum inhibitory concentration [MIC] > 2 μg/ml). Moreover, strain F4564 and F4584 exhibited high MIC to fluconazole (>256 μg/ml) and 5-flucytosine (>64 μg/ml), respectively, which were supposed to result from key amino acid substitutions Y132F and G307A in Erg11p and V58fs and G60K substitutions in Fur1p. The rare species C. haemulonii var. vulnera has emerged in China, and such drug-resistant fungal species that can cause invasive diseases require further close attention.